Effects of Hyperoxia on Mitochondrial Homeostasis: Are Mitochondria the Hub for Bronchopulmonary Dysplasia? - Xuefei, Yu; Xinyi, Zhao; Qing, Cai; Dan, Zhang; Ziyun, Liu; Hejuan, Zheng; Xindong, Xue; Jianhua, Fu (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are organelles for energy metabolism and redox reactions in the cell. Emerging data indicate that mitochondria play an essential role in physiological and pathological processes of neonatal lung development. Currently, it has been confirmed in humans and other animals that mitochondrial damage due to exposure to high concentrations of oxygen is an important factor leading to simplification of lung structural and development of bronchopulmonary dysplasia (BPD). Here, we review the progress of research done on the effects of oxygen environment on alveolar development and morphology, summarise changes in alveolar epithelial cell mitochondria under high oxygen concentrations, and discuss several mitochondrial mechanisms that may affect cell plasticity and their effects on BPD. Thus, the pathophysiological effects of mitochondria may have the potential for targeted mitochondrial and BPD therapy.